The Noetics of Nature : Environmental Philosophy and the Holy Beauty of the Visible - Foltz, Bruce V. (Book collections on Project MUSE., 2014)
Contemplative or "noetic" knowledge has traditionally been seen as the highest mode of understanding, a view that persists both in many non-Western cultures and in Eastern Christianity, where "theoria physike," or the illumined understanding of creation that follows the purification of the heart, is seen to provide deeper insights into nature than the discursive rationality modernity has used to dominate and conquer it. This book challenges both the primacy of the natural sciences in environmental thought and the conventional view that Christian theology is somehow responsible for the environmental crisis. Instead, the author concludes that the ancient Christian view of creation as iconic - its "holy beauty" manifesting the divine energies and constituting a primal mode of divine revelation - offers the best prospect for the radical reversal that is needed in the way people relate to the natural environment